Accentuation explains the difference between choice and rejection better than compatibility: A commentary on Chandrashekar et al. (2021) - Yoav Ganzach (Judgment and Decision Making)
In this comment, I examine the results of two studies (Shafir, 1993 and Chandrashekar et al., 2021) that relied on the same stimuli to examine the effect of framing selection tasks in terms of choosing versus rejecting, and discuss how, despite the failure of the later study to replicate the results of the earlier one, analyzing the similarities and differences between the two advances our understanding of the processes underlying decisions in general, and decision in such tasks in particular.